2015
DOI: 10.1155/2015/957385
|View full text |Cite
|
Sign up to set email alerts
|

The Characterization of Fish (Tilapia) Collagen Sponge as a Biomaterial

Abstract: For scaffold manufacturing, the utility of bioactive natural organic materials derived from marine products is useful and indispensable as an alternative to bovine collagen. The weakest feature of fish collagen for scaffold application is its low degeneration temperature (Td), indicating poor stability of fish collagen in mammalsin vivo. We have focused on the tropical fish tilapia as a candidate for generating a clinical scaffold. The aim of this study was to confirm theTdof tilapia type I atelocollagen (TAC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 17 publications
(17 reference statements)
2
15
0
4
Order By: Relevance
“…From our previous data [4,5] and the present results, TAC may represent not only a promising alternative to mammalian and avian collagen products but also a novel biomaterial with cell differentiation ability. The final goal with TAC is its clinical application as a scaffold in regenerative medicine.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…From our previous data [4,5] and the present results, TAC may represent not only a promising alternative to mammalian and avian collagen products but also a novel biomaterial with cell differentiation ability. The final goal with TAC is its clinical application as a scaffold in regenerative medicine.…”
supporting
confidence: 60%
“…The weakest point of fish collagen is its relatively low denaturation temperature ( ), which indicates a poor stability in clinical applications. However, our recent experiment using calorimetry revealed that of collagen solution derived from the tropical fish, tilapia (tilapia type I atelocollagen [TAC]), was 35-36 ∘ C [4], indicating that the abovementioned weak point has been completely overcome. In addition, the biological safety of TAC has been confirmed using various test methods recommended with ISO standards [5].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the lack of biomaterials with the desired physicochemical (biodegradability, swelling ratio, etc. ), mechanical (tensile strength and Young's modulus), structural (porosity), biological (biocompatibility), and immunogenic properties limit the production of highly efficient TESS (Busra, Chowdhury, Saim, & Idrus, ; Yamamoto et al, ). Moreover, due to the tailor‐made approach and regulatory requirement to culture the cells in a state of art facility, the production cost is extremely high and typically unaffordable for general patients.…”
Section: Introductionmentioning
confidence: 99%
“…The study on thermal properties of extracted cobia skin ASC showed no detection on T d of cobia skin ASC extracted from 0.5 M lactic acid when analyzed using differential scanning calorimetry (DSC) while cobia skin ASC extracted by 1.0 M lactic acid showed a T d at 37.35°C. The high T d value of cobia skin ASC extracted by 1.0 M lactic acid was correlated with high content of hydroxylation of proline in collagen among warm water fish (Yamamoto et al., 2015), whereas cold water fish has lower hydroxyproline content that acted with the interchain hydrogen bonding to stabilize the triple helical structure of collagen but it has a higher content of hydroxy amino acids, serine, and threonine (Muyonga et al., 2004). However, comparing to the T d of cobia skin ASC extracted by 1.0 M lactic acid with study by Yamamoto et al.…”
Section: Resultsmentioning
confidence: 99%